Detection of Cadmium Risk to the Photosynthetic Performance of Hybrid Pennisetum - Song, Xiliang; Yue, Xian; Chen, Weifeng; Jiang, Huixin; Han, Yanyun; Li, Xu (Frontiers in Plant Science, 2019)
Photosynthesis plays an important role in plant growth and crop yield, and the mechanisms of the effects of Cd on photosynthetic performance require more attention. The acute toxicity of Cd in soil to the photosynthetic capacity of Hybrid Pennisetum was evaluated using gas exchange parameters, A/Ci curves, light response curves and chlorophyll a ﬂuorescence transients after exposure to elevated Cd concentrations (0, 10, 20, 50, 70 and 100 mg·kg-1) for a three-month period. The results indicated that leaf Cd concentration in Hybrid Pennisetum increased with the strength of soil Cd stress and ranged from 4.9 μg·g-1 DW to 15.8 μg·g-1 DW. The accumulation of leaf Cd severely restricted photosynthesis and its nonstomatal limitation in regulating the photosynthetic performance of Hybrid Pennisetum. The leaf chloroplasts at 10 and 20 mg·kg-1 Cd concentrations showed no noticeable change, but the chlorophyll content significantly decreased by 9.0% 20.4% at 50 to 100 mg·kg-1 Cd concentrations. The Cd treatments also decreased plant ribulose-1,5-bisphosphate (RuBP) activity (Vcmax) and regeneration capacity (Jmax), triose phosphate use ability (TPU), light-saturated photosynthesis (Amax), apparent quantum yield (AQY), light saturation point (LSP) and dark respiration (Rday), but Cd treatment increased the light compensation point (LCP). The shape of chlorophyll a fluorescence transients in leaves was altered under different Cd treatments. The increased OJ phase and the decreased IP phase in fluorescence induction curves suggested that Cd toxicity inhibited both light use efficiency and photodamage avoidance ability. These results suggested that the decrease in photosynthesis through exposure to Cd may be a result of the decrease in leaf chlorophyll content, Rubisco activity, and RuBP regeneration, inhibition of triose phosphate use, reduction of the ability to use light and provide energy, and restrictions on electron transport in PSII.